Assessing the Biogas Generation Capacity of Organic Food Waste - Nnadikwe.Johnson; Onyewudiala Ibeawuchi Julius; Mbadike Columbus Asodike (Sean Institute, 2025)
Amidst growing energy demands and environmental concerns, this study explores the potential of organic food waste as a sustainable feedstock for biogas production. A laboratory-scale biogas digester was employed to investigate the anaerobic digestion of starch-rich food waste from Petroleum and Gas Engineering Department ,Imo State University Campus. The 40-day experiment examined key parameters influencing biogas yield, including volatile solids concentration, effluent density, biogas density, and reaction rate constant. Biogas production was measured using the water displacement method. This research aims to optimize biogas generation from organic food waste, providing a viable solution for community-level waste management and renewable energy production. The results highlight the potential of organic food waste as a sustainable energy source, mitigating energy crises and environmental pollution.